The CanLit Dinner Party: Feasting on Books in the Literature Classroom - Boyd, Shelley; Hollinson, Nicole (Cuizine, 2016)
This article examines the “CanLit Dinner Party”, a multimedia exhibition undertaken in an undergraduate seminar on Canadian literature where food was the central topic. Modelled in part after Judy Chicago’s art installation The Dinner Party, this 24-hour exhibition featured interpretive plates inspired by literary food scenes. As a form of experiential learning, the classroom assignment was designed to enhance the students’ critical appreciation for the art of storytelling through food, to think across disciplines, and to synthesize food-related themes studied over the course of the semester. A departure from essay-writing assignments typically found in English literature courses, the “CanLit Dinner Party” underscored food’s role as a cultural idiom by requiring students to engage with its material dimensions.